Chagall : a biography - Wullschläger, Jackie (New York : Alfred A. Knopf, 2008)
Chronicles the life of twentieth century figurative artist Marc Chagall, discussing his childhood, schooling, personal turmoil, controversial relationships, artistic impact, and other related topics.
Includes bibliographical references (p. [525]-562) and index.
Booklist starred.
Library Journal.
Publisher's Weekly.
Booklist starred, September 2008.
Choice, April 2009.
Keywords: Chagall, Marc, -- 1887-1985.; Chagall, Marc, -- 1887-1985.; Artists -- Russia (Federation) -- Biography; Artists -- Russia -- Biography